2020
DOI: 10.1007/s00355-020-01279-7
|View full text |Cite
|
Sign up to set email alerts
|

Combining absolute and relative poverty: income poverty measurement with two poverty lines.

Abstract: I study income poverty indices in a framework considering two poverty lines: one absolute line capturing subsistence and one relative line capturing social exclusion. In this framework, a set of basic axioms à la Foster and Shorrocks (1991) characterizes the class of hierarchical indices. This is a class of additive indices for which the poverty contribution of any individual depends on both her income and the income standard in her society. The key feature of hierarchical indices is to grant some form of prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
0
23
0
4
Order By: Relevance
“…SPL = Max ( Z *, α + kM ); the implication is that the poverty line is determined by the greater value between the absolute poverty line Z * and the relative poverty line α + kM , but the relative poverty line is not extremely low because the average income of the country is very low but has a minimum threshold α. Atkinson-Bourguignon and Ravallion-Chen suggested that Z * is an international poverty line of USD 1 per day (1985 PPP) or USD 1.25 per day (2005 PPP), α = 0.6 and k = 0.33; M is per capita consumption expenditure in the national economy. Based on the existing works such as Sun et al, (2018) [ 29 ], Decerf (2021) [ 30 ], Chen and Ravallion (2021) [ 31 ], and Garroway and de Laiglesia (2012) [ 32 ], this paper applies the relative poverty line standard proposed by Jolliffe and Prydz (2017) [ 33 ]: SPL = Max (USD 1.9, USD 1.0 + 0.5 × Median Consumption). …”
Section: Change Of Poverty Standard and Social Poverty Standard Spl I...mentioning
confidence: 99%
“…SPL = Max ( Z *, α + kM ); the implication is that the poverty line is determined by the greater value between the absolute poverty line Z * and the relative poverty line α + kM , but the relative poverty line is not extremely low because the average income of the country is very low but has a minimum threshold α. Atkinson-Bourguignon and Ravallion-Chen suggested that Z * is an international poverty line of USD 1 per day (1985 PPP) or USD 1.25 per day (2005 PPP), α = 0.6 and k = 0.33; M is per capita consumption expenditure in the national economy. Based on the existing works such as Sun et al, (2018) [ 29 ], Decerf (2021) [ 30 ], Chen and Ravallion (2021) [ 31 ], and Garroway and de Laiglesia (2012) [ 32 ], this paper applies the relative poverty line standard proposed by Jolliffe and Prydz (2017) [ 33 ]: SPL = Max (USD 1.9, USD 1.0 + 0.5 × Median Consumption). …”
Section: Change Of Poverty Standard and Social Poverty Standard Spl I...mentioning
confidence: 99%
“…Aun cuando existen diversos enfoques y criterios relativos al término pobreza, hay consenso respecto a que es un término que viene directamente ligado a niveles bajos de ingresos económicos (Decerf, 2021;Nolan & Whelan, 1996;Schiller, 1989). Un ejemplo de ello es la definición de pobreza relativa, la que se mide hoy como aquel nivel de ingresos inferior a la mitad o menos de la media de un grupo poblacional.…”
Section: Marco Teórico Conceptualunclassified
“…Un ejemplo de ello es la definición de pobreza relativa, la que se mide hoy como aquel nivel de ingresos inferior a la mitad o menos de la media de un grupo poblacional. Al margen de esto, se han ido elaborando otras formas de aproximación al fenómeno de la pobreza, con índices de pobreza que no sólo tienen en cuenta los ingresos, sino también el gasto, el consumo, la educación, etc., lo que también varía en función del contexto analizado, el país o la sociedad (Decerf, 2021).…”
Section: Marco Teórico Conceptualunclassified
“…Income poverty can be classified as absolute or relative (Decerf, 2017). According to De (2017), absolute poverty is defined as a shortage of a person's basic needs and services, which are mostly linked to food, clothes, and housing.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on relative poverty lines with an income threshold that is dependent on the income standard. An individual is considered poor if his/her income falls below the standard income of his community (Decerf, 2017). This approach of poverty is regarded as a measure of inequality as individuals are considered poor if they are economically or socially disadvantaged relative to other people in their community (De, 2017).…”
Section: Introductionmentioning
confidence: 99%